Effects of Water and Nutrients on the Postharvest Quality and Shelf Life of Citrus - Mark A. Ritenour; Wilfred F. Wardowski; David P. Tucker (EDIS)
Irrigation and fertilization are important components of commercial citrus production. Irrigation is necessary to adequately replenish soil water lost through evaporation and transpiration. Fertilizers replace nutrients removed during harvest and through leaching. They also maintain tree growth and vigor. Optimum management of both is critical for obtaining maximum yield. Irrigation and fertilization practices can also have significant impacts on fruit quality and shelf life during harvest, packinghouse operations, storage, and distribution. These include effects on fruit color, texture, disease susceptibility, juice composition, and the development of physiological disorders. 1. This document is HS942, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: July 2002. Revised publication date: August 2003.